Ethnobotany of sacred plants and agricultural rituals among the Kanayatn Dayak in Ambawang Village, West Kalimantan, Indonesia (Biodiversitas Journal of Biological Diversity, 2025)
Abstract. Hasanah SU, Syamswisna, Candramila W. 2025. Ethnobotany of sacred plants and agricultural rituals among the Kanayatn Dayak in Ambawang Village, West Kalimantan, Indonesia. Biodiversitas 26: 2882-2894. The Dayak Kanayatn people in West Kalimantan, Indonesia, uphold their customs, reflecting their dependence on nature through traditional ceremonies that utilize plants, which are vital for their cultural and heritage conservation. These rituals not only have social value but also aid in biodiversity conservation through locally inherited wisdom. This research documents the use of plants in Bahuma, the traditional agricultural rituals of the Dayak Kanayatn community, conducted in Ambawang Village, Kubu Sub-district, Kubu Raya District, West Kalimantan, to support the preservation of their traditions and ethnobotanical knowledge. The study took place from March to July 2023 across four hamlets (Tanah Kuning, Parit Sembilan, Kuala Ambawang, and Medan Sri). The study employed surveys, field observations, semi-structured interviews with key informants, and documentation of plant specimens used in ceremonies. Data analysis qualitatively categorized agricultural rituals and their associated plants, organizing the information by name, classification, parts utilized, significance in rituals, and collection locations. The community preserves the Adat Bahuma agricultural ritual, comprising six key ceremonies related to rice planting and involving 24 plant species, primarily from the Araceae and Poaceae families. While reflecting their spiritual connection to rice cultivation and reliance on local plants, the Dayak Kanayatn community faces challenges in conserving declining species crucial to their cultural practices.
Keywords: Agricultural traditional rituals, Bahuma tradition, Dayak Kanayatn, ethnobotany